Hubungan Kepadatan Tumor-Associated-Macrophages dan TumorAssociated-Neutrophils dengan Karakteristik Klinikohistopatologi pada Pasien Limfoma Hodgkin - Nadya Virana Putri; Neti; Riana Sari Puspita Rasyid; Krisna Murti (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2021)
BackgroundThe development and aggressiveness of tumor cells were influenced by tumor microenvironment. Tumor-Associated-Macrophages(TAMs) and Tumor-Associated-Neutrophils (TANs) are components of tumor microenvironment, contribute to development and growthof tumor cells. The aim of this research was to analyse correlation of TAMs and TANs densities with clinicohistopathologiccharacteristics of patients i.e. age, gender, location, and subtype.MethodsA case series was conducted. The samples were paraffin blocks of Hodgkin lymphoma patients at Anatomic Pathology DepartmentFaculty of Medicine Universitas Sriwijaya/RSUP Dr. Mohammad Hoesin Palembang. Among 44 cases of Hodgkin lymphomadiagnosed from 1stJanuari 2015 to 30th October 2019, only 31 cases were included. Immunohistochemistry was performed by usinganti-CD163 antibody and neutrophils were identified by morphologic appearances. The results were correlated to characteristicfactors. Statistical analysis was performed using Spearman and Lambda test with significant consideration if p<0.05.ResultsThe study results showed 30 cases of classical Hodgkin lymphoma (CHL) and 1 case of NLPHL. CHL has only 3 variants LR(lymphocyte-rich) (60%), MC (mixed-cellularity) (26.7%), and NS (nodular sclerosis) (13.3%). Hodgkin lymphoma is most commonlyfound in males (61.3%). Tumor were mostly found in the head and neck, and patient ages were majority in the age group 20-29 years,40-49 years, and over 50 years. Spearman test showed there was a significant correlation between density of TAMs with ages(p=0.043).ConclusionHigh density of TAM was correlated with age, however, there was no correlation between TAN and clinicohistopathologiccharacteristics of Hodgkin lymphoma.